Logikperspektivet – ett försök till analysmetod - Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2012)
The article explores the logics approach to critical explanation, as it has been described by Jason Glynos and David Howarth (2007). The approach addresses the question of applying discourse theory to empirical phenomena, and it suggests three different logics – social, political and fantasmatic – that work to help the researcher construct critical explanations of practices and regimes. In the article the logics approach is described, exemplified and discussed in relation to the discipline of ethnology.